A Quality Improvement Project Regarding Breastfeeding Practices Among Postnatal Mother of Infants Who are Admitted in SNCU of A Selected Health Care Setting - Papiya Bera Saha; Smritikana Mani; Govinda Chandra Das (Indonesian Journal of Global Health Research, 2020)
Breast milk is unquestionably the best milk for the baby. From 1sthour to first six months of life, infants should be exclusively breastfed to achieve growth & development, but most of the time this objective is not fulfilled. So to improve the practice of breastfeeding we collected the baseline data from selected unit ,we observed that the breastfeeding rate of the postnatal mothers is only 48%. Even after a lot of effort ,we could not achieve breastfeeding practice in our SNCU before starting our project. Then we started structured and plannedprogramme in the form of PDSA cycle for 45 days. The study was adopted to increase breastfeeding practice rate from 48% to 80% in 6 weeks among mother in the infants of SNCU. In this QI project applied on 25 postnatal mother of infants who are admitted in SNCU of RG Kar Medical College & Hospital,Kolkata. Data was collected by valid feeding register and observation checklist. For the implementation of the project, a team was formed & a meeting was carried out among the team members. The team found the root cause analysis by fishbone model. The team members decided to carry out PDSA cycles at the interval of 15 days for carrying out three consecutive cycles, Where the first cycle deals with motivating the health care staffs ,mothers in SNCU as well as postnatal ward, the second cycle deals with providing IEC materials and privacy of themother during breastfeeding and the third PDSA cycle deals with involving the family members of the mother. After 1st PDSA cycle we have achieved an increase of only 4% of breastfeeding practice rate in the selected unit.After 2nd PDSA cycle we have achieved an increased rate of 14% of breastfeeding practice. The team observed even after 2nd PDSA cycle we did not achieve our goal, then after involving the family members in the third PDSA cycle ,we have observed a dramatic increase in the breastfeeding practice rate upto 80%. The study concluded that simple planned QI group effort can improve the breastfeeding practice rate in the any unit. Keywords: quality improvement, breastfeeding practices, postnatal mother, PDSA, SNCU, health care settings